(untitled) (Research, Society and Development, 2022)
Proprioceptive neuromuscular facilitation was developed by Dr. Herman Kabat and Margaret in 1940. It is more than a simple technique, it is a treatment philosophy based on the concept that every human being, including the disabled, has untapped potential. The study is an integrative review to objectived verify the effects of proprioceptive neuromuscular facilitation on sarcopenia in the elderly, through publications selected from the LILACS, PubMed, and Scielo databases in Portuguese and English. After the application of the criteria, 5 articles were included in the review, those that approached the concepts about sarcopenia in the elderly and that explained the FNP and the effect of the technique on sarcopenia in the elderly. Through this review it was found in the reviewed studies that FNP has a significantly positive effect on the maintenance of muscle fiber in the elderly with sarcopenia, improving strength and trophism, proving to be effective in the treatment of sarcopenia in the elderly. Thus, FNP may be a physiotherapeutic intervention both preventive and restoring the quality of life of the elderly, thus minimizing the effects of sarcopenia and the impacts brought on the lives of the elderly. However, further clinical research with a larger number of older people associated with the application of the technique and other techniques is suggested